Tintenfass und Teleskop: Galileo Galilei im Schnittpunkt wissenschaftlicher, literarischer und visueller Kulturen im 17. Jahrhundert - Albrecht, Andrea; Cordibella, Giovanna; Remmert, Volker R. (Spectrum Literaturwissenschaft, 2014)
This volume explores the image of Galileo Galilei’s as a scientist of the early modern age along with cultural perceptions of his discoveries and writings. It examines the interconnections between scientific theories and practices and their textual and visual representations.
Includes index
Keywords: Galilei, Galileo -- 1564-1642; Electronic books; Konferenzschrift; Aufsatzsammlung; Galilei, Galileo